GAMBARAN PENGETAHUAN SANTRI TENTANG PERSONAL HYGIENE DALAM MENCEGAH SKABIES - Salawaty Salawaty; Arneliwati Arneliwati; Sri Wahyuni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2020)
The knowledge about personal hygiene is one of the factors that influence someone on scabies preventing and spreading. The purpose of this research was to know the description of students’knowledge about personal hygiene at dormitory. The design of this research was descriptive. The sample of this research were 154 respondents which was taken by stratified random sampling technique and appropriate with inclusion criteria. The instrument of this research were questionnaire. The questionnaire consisted of the respondents characteristic such us class, age, gender, duration of living in the dormitory, and knowing the description of students’ knowledge about personal hygiene in preventing scabies. The result of this research, the majority of respondent in the age of 13 were 75 students (48.7%), the gender was almost between male and female students. There were 76 male (49.3%) and 78 female (50.7%), for class distribution, 88 students from seven grade (57.1%). The long duration of living in dormitory data, 88 students (57.1%) lived in the dormitory less than 1 year. Students of had good knowledge about personal hygiene in preventing scabies, that were 79 (51.3%). The good knowledge is not enough to prevent scabies, but the personal hygiene to decrease because need education for preventing of scabies disease.Keywords : scabies, knowledge, personal hygiene, preventing